THE INTERPLAY OF CLASS, CASTE, AND IDEOLOGY IN SHAPING POLITICAL IDENTITIES IN KARNATAKA. - Madar, Dharmanna; G, Basavaraja (ShodhKosh: Journal of Visual and Performing Arts, 2024)
From 1956 to 2020, when the state transitioned from linguistic rearrangement to a centre of socio-political contestation, this study explores the intricate interactions between class, caste, and ideology in forming political identities in Karnataka. The paper examines how conflicting ideological frameworks—such as socialism, social justice, and Hindutva—interact with intersecting caste and class hierarchies to affect political mobilization and voter behavior. It does this by drawing on historical analysis, election statistics, and qualitative fieldwork. It contends that, in addition to neoliberal economic changes and urbanization, the assertion of Other Backward Classes (OBCs), Dalits, and marginalized groups has increasingly transformed Karnataka’s political environment, which was historically dominated by the dominant castes (Lingayats and Vokkaligas). According to the analysis, caste is still a fundamental axis of political identity, but class-based concerns, especially in urban informal labor markets and rural problems, mitigate its salience. From the socialist movements of the 1970s and 1980s to the Hindu nationalist ambition of the BJP, ideological narratives have purposefully allied themselves with or opposed these identities in order to gain power. Ideologies can be used as a weapon to transcend or strengthen caste-class divisions, as seen by the BJP’s Hindutva politics and the Janata Dal’s social justice agenda. The flexibility of identity politics in the state is further illustrated by case studies of linguistic subnationalism, land reforms, and reservation disputes. However, the analysis highlights ambiguities in Karnataka’s democratic trajectory by identifying tensions between the ideology’s emancipatory ideals and their co-optation by elite groups. Structural injustices endure in spite of progressive programs, made worse by neoliberal policies and dispersed opposition. The article’s conclusion provides a more comprehensive understanding of the contradictions of identity-driven democracy in India by pointing out that Karnataka’s political identity is a dynamic, contested landscape where caste solidarity, class interests, and ideological hegemony converge.